Geometry and Kinematics Characteristics of Strike-Slip Fault Zone in Complex Structure Area: A Case Study From the South No. 15 Strike-Slip Fault Zone in the Eastern Sichuan Basin, China - Cheng, Xiaoyun; Ding, Wenlong; Pan, Lei; Zou, Yutao; Li, Yuntao; Yin, Yixing; Ding, Shihao (Frontiers in Earth Science, 2022)
The No. 15 strike-slip fault zone in the eastern Sichuan Basin has undergone multistage tectonic evolution and shows complex structural characteristics. There are almost no previous studies on strike-slip faults in the eastern Sichuan Basin. Based on highly precise 3D seismic section, coherent attribute slice and time slice, the geometric and kinematic characteristics of the fault are analyzed. The dynamic characteristics are analyzed based on the structural style of the superimposed development model and the nature and activity intensity of strike-slip faults in different periods. The research results show that the profile of the No. 15 strike-slip fault mainly shows a subvertical fracture, positive flower structure and negative flower structure and a composite flower structure with positive and negative flower structures superimposed on each other in the upper and lower planar sections with linearly outspread and zonal distribution characteristics; spatially, there is a "ribbon" effect and a "dolphin" effect. the left strike-slip distance of the TS interface is 0.462 km, and the right strike-slip distance of the TP2 interface is 0.782 km. The strike-slip fault experienced at least three active stages of superimposed deformation during its formation and reconstruction, among which episode II in the middle Caledonian movement was the main active stage of the No. 15 strike-slip fault zone. This study of the structural style and genetic mechanism of a strike-slip fault zone is of guiding significance to the exploration and development of strike-slip fault-controlled reservoirs in the study area.